Tragedies on natural resources a commons and anticommons approach - Coelho, Manuel (2010)
Ambiguous concepts blur analytical and policy prescription clarity. In the literature on Natural Resources it would be difficult to find a concept as misunderstood as commons. This paper clarifies this confusion and establishes an adequate conceptualisation. A typology of property-rights regimes relevant to common property resources is presented and a new concept – anticommons - is introduced. The reflex of this regimes distinction on the design of the natural resources policy is discussed and this conceptualisation is used to study exemplar cases in the area of fisheries and aquaculture policy in Portugal.